(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2020)
The main goal of this study was to examine the spectrum of Enterococci that cause urinary tract infection in newborns. This study was conducted during September 2018 to November 2018 at Prince Sattam Bin Abdul Aziz University. A total of 317 urine samples were taken from newborns admitted to the Children’s Hospital in the city of Riyadh, Kingdom of Saudi Arabia. In total, 30 (9.5%) Enterococcal strains were isolated from 317 samples. Of these, 17 (56.6%) were from male and 13 (43.4%) were from female patients. From antibiotic sensitivity assay, it was observed that all of the isolates were resistant to clindamycin. But Imipenem and Augmentin were found highly sensitive. So, these sensitive antibiotics can be used for the treatment of newborns UTIs caused by the enterococcal strains. Dhaka Univ. J. Pharm. Sci. 19(2): 119-124, 2020 (December)